ANALISIS DAMPAK NILAI CR, DER DAN EPS TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERBANKAN DI BURSA EFEK INDONESIA (BEI) - Galih Gerranda Ramadhani; Sri Hermuningsih; Gendro Wiyono (Jurnal MANAJERIAL, 2022)
The current capital market has experienced rapid development and plays an important role in mobilizing funds from people who want to invest in the capital market. In a broad sense, investment is a sacrifice made at this time with the aim of obtaining a higher value in the future. Based on empirical evidence linking fundamental factors with stock returns, they still show different results, so further research needs to be done to prove how the influence of the four fundamental factors (EPS, DER, CR and ROA) on stock returns, especially in the banking industry sector in Indonesia. Indonesia stock exchange. This makes researchers interested in knowing the extent of the influence of Current Ratio, Dept. Equity Ratio and Earning Per Share on Stock Return. Profitability (ROA). The population used in this study is conventional banks in 2016-2020 or for 5 years. The sampling technique used was purposive sampling by meeting the criteria for being listed on the Indonesian stock exchange as a banking company and having clear financial statements. The analytical technique used in this research is the SEM analysis method. The test results show that the Current Ratio has no effect on Return On Assets, but has a positive effect on stock returns. The Dept. Equity Ratio variable has an effect on Return On Assets, but has no effect on stock returns. Earning Per Share variable has an effect on Return On Assets and there is an effect on Earning Per Share on stock returns. Return on Assets has no effect on stock returns. The Return On Asset variable does not moderate the effect of Current Ratio, Dept. Equity Ratio and Earning Per Share on stock returns because the p-value of the moderating effect is 0.05. Keyword: Current Ratio; Dept Equity Ratio; Earning Per Share; Return On Asset; return saham